2015
DOI: 10.1097/mpg.0000000000000792
|View full text |Cite
|
Sign up to set email alerts
|

Use and Safety of Erythromycin and Metoclopramide in Hospitalized Infants

Abstract: Objective Prokinetic medications are used in premature infants to promote motility and decrease time to full enteral feeding. Erythromycin and metoclopramide are the most commonly used prokinetic medications in the neonatal intensive care unit (NICU), but their safety profile is not well defined. Methods We conducted a large retrospective cohort study using data from 348 NICUs managed by the Pediatrix Medical Group. All infants exposed to ≥1 dose of erythromycin, metoclopramide, or both, from a cohort of 887… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
21
0
2
Order By: Relevance
“…(11) In 2009, the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition and the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition published clinical practice guidelines for pediatric gastroesophageal reflux, which warned of H2 blockers’ association with NEC and presented them as inferior to proton pump inhibitors (PPIs). (19)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(11) In 2009, the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition and the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition published clinical practice guidelines for pediatric gastroesophageal reflux, which warned of H2 blockers’ association with NEC and presented them as inferior to proton pump inhibitors (PPIs). (19)…”
Section: Discussionmentioning
confidence: 99%
“…(19) A 2014 Cochrane review found moderate evidence to support the use of PPIs over H2 blockers in the treatment of pediatric gastroesophageal reflux, but noted the difficulty in drawing conclusions due to a lack of placebo-controlled trials, especially in infants. (20) Prokinetics previously studied in infants include erythromycin and metoclopramide, but neither are approved for this use by the Food and Drug Administration and both have serious potential side effects including pyloric stenosis and dopaminergic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythromycin is commonly indicated within the neonatal population for prophylaxis following Chlamydia trachomatis infection [18] in preventing conjunctivitis or pneumonia and in the treatment of pertussis [14]. In addition, erythromycin has also been utilised in the treatment of gastrointestinal dysmotility within this population [10].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for use in pediatric GER is confl icting as some studies show that there is no signifi cant improvement in symptoms and esophageal pH measurements compared to placebo while others show signifi cant improvement [ 33 , 34 ]. In the NICU setting, there may be an increased risk for adverse events compared to erythromycin [ 35 ]. Metoclopramide is used frequently to treat postoperative nausea and vomiting [ 36 ].…”
Section: Metoclopramidementioning
confidence: 99%